Acquisition of complement fixing antibodies targeting Plasmodium falciparum merozoites in infants and their mothers in Uganda - Mortazavi, Susanne E.; Lugaajju, Allan; Nylander, Maria; Danielsson, Lena; Tijani, Muyideen Kolapo; Beeson, James G.; Persson, Kristina E. M. (Frontiers in Immunology, 2023)
Background: Antibody-mediated complement fixation has previously been associated with protection against malaria in naturally acquired immunity. However, the process of early-life development of complement-fixing antibodies in infants, both in comparison to their respective mothers and to other immune parameters, remains less clear. Results: We measured complement-fixing antibodies in newborns and their mothers in a malaria endemic area over 5 years follow-up and found that infants' complement-fixing antibody levels were highest at birth, decreased until six months, then increased progressively until they were similar to birth at five years. Infants with high levels at birth experienced a faster decay of complement-fixing antibodies but showed similar levels to the low response group of newborns thereafter. No difference was observed in antibody levels between infant cord blood and mothers at delivery. The same result was found when categorized into high and low response groups, indicating placental transfer of antibodies. Complement-fixing antibodies were positively correlated with total schizont-specific IgG and IgM levels in mothers and infants at several time points. At nine months, complement-fixing antibodies were negatively correlated with total B cell frequency and osteopontin concentrations in the infants, while positively correlated with atypical memory B cells and P. falciparum-positive atypical memory B cells. Conclusion: This study indicates that complement-fixing antibodies against P. falciparum merozoites are produced in the mothers and placentally-transferred, and they are acquired in infants over time during the first years of life. Understanding early life immune responses is crucial for developing a functional, long lasting malaria vaccine.